STUDI PERBANDINGAN SHELTER TERHADAP RESPON PASCA PRODUKSI LARVA LOBSTER PASIR Panulirus homarus PADA KONTAINER SISTEM RESIRKULASI - Yudha Lestira Dhewantara; Fisrty Rahmatia; Armen Nainggolan (Universitas Sriwijaya, 2021)
Sand lobster (Panulirus homarus) is a commodity with high economic value. The demand for sea crayfish consumption continues to increase from year to year. This is due to the decreasing availability of lobster and its effect on activities in catching lobster in the wild. Many lobster cultivation efforts have been carried out in an effort to meet the demand for lobster. This study aims to analyze the effect of the use of individual square shelters and PVC pipes on the post-production response of sand lobster Panulirus homarus in a recirculation system container. This research had been carried out from December 2020 to July 2021 at the Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Satya Negara Indonesia. This experiment used a completely randomized design (CRD) consisting of three and each treatment had four replications. The treatments consist of: Treatment A: PVC pipe shelter; Treatment B: Individual Shelter; Treatment C: Control (without shelter). The use of different number of shelters has an effect on survival, specific growth rate, carapace length and feed conversion ratio of sand lobster post larvae. Treatment A gave the best production performance with survival, carapace length and feed conversion ratio of 88.89%±19.24a, 95.76±2.43 mm, 104.02±11.49 mm, and 6 ,7 ± 0.1 g/day. Keywords: Sand Lobster (Panulirus homarus), Shelter, Recirculation System, Growth